การสร้างแบบจำลองและการออปติไมซ์ของระบบทำความเย็นด้วยโพรพิลีน - มณีรัตน์ กาวาฮารา (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
This research is mainly studied on Propylene Refrigeration System, which is one of the refrigeration processes of Thai Olefins Plant. Modeling based on the actual process and optimization of operating condition is included. The propylene refrigeration cycle is closed loop system. This cycle propylene is recycled to process gas compressor. The propylene refrigerant compressor is a four-stage centrifugal machine, which is designed to supply propylene refrigeration at-40,-21, -7 and degrees C, respectively. The compressor is driven by a variable speed steam turbine. If we can minimize the energy consumption of the compressor-turbine, it will be very cost effective in terms of operation. The aim is to reduce the compressor energy consumption, resulting in reduction of high-pressure steam consumption in steam turbine. Aspen Plus version 9.3-1 issued to create a model and optimize the propylene refrigeration system. First, we created an accurate model based on design data and then we tested this model with actual operating data. We found that it is not verified. Therefore, we adjusted process parameter the data reconciliation. We then used the resulting model to determine the proper operating conditions using the compressor energy consumption as our criteria for optimization. It was found that a combination of the first stage suction pressure of the compressor and the proper flow distribution of propylene in the compressor could reduce the energy consumption. The high-pressure steam consumption is reduced by 1,930.133 tons per year and the energy costs reduced by 829,957.10 Baths per year. Case studies, to determine the costs of individual refrigerant level, are conducted by increasing the flow rate by per hour. The most expensive is fist level (at-40 degree C), about 1,368,028.98 Baths/ton/year. The second level (at-21 degree C) and third level (at-7 degree C), is cheaper about 1,155,349.59 and 1,016,817.33 Baths/ton/year respectively. And fourth level (at 7 degree C) is the cheapest about 870,168.36 Baths/ton/year.